The spatial control of Torso RTK activation: a C-terminal fragment of the Trunk protein acts as a signal for Torso receptor in the Drosophila embryo. - Casali, A.; Casanova, J. (Development, 2001)
Regulated activation of receptor tyrosine kinases depends on both the presence of the receptors at the cell surface and on the availability of their ligands. In Drosophila, the torso tyrosine kinase receptor is distributed along the surface of the embryo but it is only activated at the poles by a diffusible extracellular ligand generated at each pole that is trapped by the receptor, thereby impeding further diffusion. Although it is known that this signal depends on the activity of several genes, such as torso-like and trunk, it is still unclear how is generated. The identification of the signal responsible for the torso receptor activation is an essential step towards understanding the mechanism that regulates the local restriction of torso signalling. Here we report that a fragment containing the carboxy-terminal 108 amino acids of the trunk protein retains trunk activity and is sufficient to activate torso signalling. We also show that this fragment bypasses the requirements for the other genes involved in the activation of the torso receptor. These results suggest that a cleaved form of the trunk protein acts as a signal for the torso receptor. We therefore propose that the restricted activation of the torso receptor is defined by the spatial control of the proteolytic processing of the trunk protein.